2008
DOI: 10.1073/pnas.0802328105
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of the genes encoding the polymorphic Plasmodium falciparum apical membrane antigen 1: Implications for vaccine design

Abstract: Immunization with the highly polymorphic Plasmodium falciparum apical membrane antigen 1 (PfAMA1) induces protection in animals but primarily against parasites that express the same or similar alleles. One strategy to overcome the obstacle of polymorphism is to combine PfAMA1 proteins representing major haplotypes into one vaccine. To determine the minimum number of haplotypes that would confer broad protection, we sequenced the coding region of PfAMA1 from 97 clones from around the world and 61 isolates from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
114
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 24 publications
9
114
1
Order By: Relevance
“…A recent phase 2b AMA1 vaccine trial in 1-6-y-old children in Mali found 64% efficacy against malaria caused by vaccine-like strains, underscoring its potential as a malaria vaccine (41). Unfortunately, AMA1 displays immense antigenic variation: .10% of its residues are polymorphic, and .200 unique haplotypes have been identified (42,43). A crystal structure of AMA1 reveals that the protein consists of three domains that present two immunologically distinct regions: a conserved face, consisting of a cluster of largely conserved epitopes along domain I and III, and a polymorphic face, consisting of a cluster of highly polymorphic epitopes along domain II (44,45).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent phase 2b AMA1 vaccine trial in 1-6-y-old children in Mali found 64% efficacy against malaria caused by vaccine-like strains, underscoring its potential as a malaria vaccine (41). Unfortunately, AMA1 displays immense antigenic variation: .10% of its residues are polymorphic, and .200 unique haplotypes have been identified (42,43). A crystal structure of AMA1 reveals that the protein consists of three domains that present two immunologically distinct regions: a conserved face, consisting of a cluster of largely conserved epitopes along domain I and III, and a polymorphic face, consisting of a cluster of highly polymorphic epitopes along domain II (44,45).…”
mentioning
confidence: 99%
“…A crystal structure of AMA1 reveals that the protein consists of three domains that present two immunologically distinct regions: a conserved face, consisting of a cluster of largely conserved epitopes along domain I and III, and a polymorphic face, consisting of a cluster of highly polymorphic epitopes along domain II (44,45). Previous studies suggested that no fewer than 6-10 strains of AMA1, and possibly many more, must be included in a polyvalent vaccine to provide sufficient allelic coverage for broad protection (42,43,46). However, several studies developed polyvalent formulations of AMA1, using two to six strains, and demonstrated significant cross-reactivity and protection relative to the monovalent vaccine of any single strain (47)(48)(49)(50).…”
mentioning
confidence: 99%
“…The potential of AMA1 as a malaria vaccine candidate has been demonstrated in rodent models of malaria with both strain-specific [87][88][89] and cross-protective [90] protection observed. High levels of polymorphism in AMA1 [8,91,92] due to strong balancing selection [93] has resulted in hundreds of distinct AMA1 haplotypes; this might indicate that the development of a broadly effective AMA1-based malaria vaccine will be difficult. However, little is known about the antigenic diversity of AMA1 and recent studies suggest that immunization with a small number of different alleles might give broad reactivity [94,95].…”
Section: Apical Membrane Antigen 1 (Ama1)mentioning
confidence: 99%
“…This analysis has also been adapted to understand relationships among haplotypes of several malaria vaccine candidates [8,91,92,226]. A study of 150 AMA1 sequences by Xin Zhuan Su and colleagues demonstrated that they clustered into six distinct subgroups.…”
Section: Clustering Patternsmentioning
confidence: 99%
“…The LMIV at NIH in collaboration with MRTC in Mali has applied a clustering algorithm to AMA1 sequence data from isolates around the world and identified six distinct populations based primarily on geographic area that in limited testing have induced non-cross-protective antibodies, thus constituting a minimum requirement for the number variants needed for a vaccine. 29 The Biomedical Primate Research Center (BPRC) in The Netherlands has synthesized three "diversity covering" versions of AMA1 encompassing 97% of the amino acid variability observed in nature and conducted preliminary studies in rabbits showing the induction of crossinhibitory antibodies. 30 Similar studies are underway at the La Trobe University and at the Walter and Eliza Hall Institute of Medical Research in Australia.…”
Section: Antigen Designmentioning
confidence: 99%